1991
DOI: 10.1007/bf00169549
|View full text |Cite
|
Sign up to set email alerts
|

N2-Acetylphenelzine : effects on rat brain GABA, alanine and biogenic amines

Abstract: The neurochemical properties of N2-acetylphenelzine were compared with those of phenelzine in a rat model. N2-Acetylphenelzine is a relatively potent inhibitor of monoamine oxidase-A and -B and causes increases in whole-brain levels of noradrenaline and 5-hydroxytryptamine, and decreases in homovanillic acid, 5-hydroxyindole-3-acetic acid, and 3,4-dihydroxyphenylacetic acetic after acute i.p. administration of the drug. Phenelzine is a more potent monoamine oxidase inhibitor than is N2-acetylphenelzine. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Experiments in our laboratories have indicated that the GABA-elevating effect of PLZ is rather dramatic, occurring at reasonably low doses and remaining for lengthy periods after a single dose of PLZ McKenna et al, 1991;Parent et al, 2000]. Behavioral studies in the elevated plus maze test with PLZ and an analog (N 2 -acetylPLZ) which inhibits MAO but does not elevate brain GABA indicated that the antianxiety actions of PLZ are directly correlated to its ability to elevate brain GABA [Paslawski et al, 1996].…”
Section: Resultsmentioning
confidence: 99%
“…Experiments in our laboratories have indicated that the GABA-elevating effect of PLZ is rather dramatic, occurring at reasonably low doses and remaining for lengthy periods after a single dose of PLZ McKenna et al, 1991;Parent et al, 2000]. Behavioral studies in the elevated plus maze test with PLZ and an analog (N 2 -acetylPLZ) which inhibits MAO but does not elevate brain GABA indicated that the antianxiety actions of PLZ are directly correlated to its ability to elevate brain GABA [Paslawski et al, 1996].…”
Section: Resultsmentioning
confidence: 99%
“…PLZ increases brain levels of the classical monoamine neurotransmitters (9)(10)(11)(12) and trace amines (phenylethylamine (PEA), tyramine and tryptamine) (13). However, it also inhibits GABA-transaminase (GABA-T) (10,14,15) and markedly increases brain levels of the inhibitory amino acid transmitter Á-aminobutyric acid (GABA) (10,(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…However, it also inhibits GABA-transaminase (GABA-T) (10,14,15) and markedly increases brain levels of the inhibitory amino acid transmitter Á-aminobutyric acid (GABA) (10,(14)(15)(16)(17)(18)(19)(20)(21). GABA-T requires pyridoxal phosphate (PLP) as a cofactor, and PLZ also inhibits a number of other PLP-dependent enzymes (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…N 2 -Acetylphenelzine, a derivative of the nonselective MAO-inhibiting antidepressant/antipanic drug phenelzine, has been shown to be a relatively potent non- MAO-A and MAO-B [McKenna et al, 1991] and to be neuroprotective [Urichuk et al, 1998]. N 2 -acetylphenelzine is also devoid of the brain γ-aminobutyric acid (GABA)-elevating effects seen with phenelzine [McKenna et al, 1991].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, such compounds would be expected to be devoid of GABAelevating activities, since this effect of phenelzine requires the presence of an unsubstituted hydrazine group [McKenna et al, 1991]. Furthermore, the possibility that subtle rearrangements in the chemical structures might provide compounds that could be selectively taken up and sequestered by certain cell types, thereby leading to cell-or tissue-specific effects, was considered.…”
Section: Introductionmentioning
confidence: 99%